2020
DOI: 10.1108/prt-09-2019-0080
|View full text |Cite
|
Sign up to set email alerts
|

Red cabbage anthocyanins content as a natural colorant for obtaining different color on wool fibers

Abstract: Purpose Finding blue colorants from natural sources is extremely difficult and, usually, the anthocyanin compounds are used for producing the blue color. This study aims to apply the Red Cabbage as a natural colorant to obtain different colors on wool yarn, as well as specify the optimum dyeing condition by response surface methodology for obtaining a blue color. Design/methodology/approach The effect of dyeing process parameters such as mordant concentration, dyeing time, pH of dyeing bath and dyeing temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The colorfastness to washing slightly improved to Grade 4 after the oxidation treatment, which suggests that excellent absorption of lignin into wool fibers was achieved, increasing the colorfastness to washing. The colorfastness to washing achieved for the lignin sulfonate dyed wool fabrics is quite satisfactory as wool fabrics dyed with natural dyes also show similar colorfastness to washing grade. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The colorfastness to washing slightly improved to Grade 4 after the oxidation treatment, which suggests that excellent absorption of lignin into wool fibers was achieved, increasing the colorfastness to washing. The colorfastness to washing achieved for the lignin sulfonate dyed wool fabrics is quite satisfactory as wool fabrics dyed with natural dyes also show similar colorfastness to washing grade. , …”
Section: Resultsmentioning
confidence: 99%
“…Natural dyes extracted from leaves of pomegranate, Berberis thunbergia, hibiscus flowers, Hibiscus rosa-sinensis, Crocus sativus, skins/peel of Citrus sinensis L., and various fruits, including myrobalan, chamomiles, and peanut shell, are also studied as an alternative to synthetic dyes. Anthocyanin pigments extracted from peels/skins of various fruits, including Brassica oleracea L., purple sweet potatoes, red cabbages, and dragon berries, have been studied for the dying of wool that produces a variety of colors. Tannins and other flavonoids are advantageous as some of them have antioxidant and antibacterial properties that make the treated fabric multifunctional .…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al (2020) and Varjani et al (2020) reported that the textile industry alone produced 0.7 million tons of textile dyes which are lost to effluents each year, thus creating 2.15 billion tons of dyepolluted wastewater. Textile dyes are natural and synthetic compounds that can absorb radiation of light within the visible spectrum, and they are consist of two main components, chromophores and auxochromes (Barani et al, 2019;Maleki and Barani, 2019;Barani and Maleki, 2020;Haji and Naebe, 2020). Chromophores are made up of different functional groups (O=(C 6 H 4 ) = O, -C=O, -N=N-and -NO 2 ) and are responsible for giving color properties to the dyes.…”
Section: Textile Dyesmentioning
confidence: 99%
“…These dyes are extracted from plants, and their effluents can be either recycled or their residues when mix with soil can act as fertilizer (Swami et al , 2014; El-Khatib et al , 2021). These colorants have wide spectrum of colors, but also by tinting these can also provide new shades that can be possible substitutes of synthetic dyes (Barani and Maleki, 2020). Hence, the revival of the art of natural dyes is now the global demand, particularly in the present pandemic situation (Prado et al , 2020).…”
Section: Introductionmentioning
confidence: 99%